Pengaruh Penerapan Corporate Social Responsibility terhadap Profitabilitas dengan Sustainability Report sebagai Moderasi - Panji Dharma Agung P; Akhmad Naruli; Miladiah Kusumaningarti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) implementation on profitability, with the Sustainability Report acting as a moderating variable, at PT Sinergi Gula Nusantara, Ngadirejo Sugar Factory, during the 2019–2023 period. Profitability was measured using Return on Assets (ROA) and Net Profit Margin (NPM), CSR was assessed through the PROPER rating, and the Sustainability Report was evaluated using a disclosure index based on the Global Reporting Initiative (GRI) standards. The research utilized a quantitative descriptive method and Moderated Regression Analysis (MRA) to test the relationships between the variables. The findings revealed that CSR had a positive and significant effect on both ROA and NPM. However, the study found that the Sustainability Report did not moderate the relationship between CSR and ROA, indicating that the sustainability disclosures had no significant impact on improving ROA. In contrast, the Sustainability Report was able to moderate the relationship between CSR and NPM, strengthening the influence of CSR on profitability as measured by NPM. This suggests that sustainability reporting plays a critical role in enhancing the positive effects of CSR on financial performance, particularly in terms of profitability indicators such as NPM. The study provides valuable insights for companies aiming to integrate CSR practices and sustainability reporting to achieve improved financial performance and long-term sustainability.